2020
DOI: 10.1111/jgh.15307
|View full text |Cite
|
Sign up to set email alerts
|

Targeting interleukin 6 signaling by monoclonal antibody siltuximab on cholangiocarcinoma

Abstract: Background and Aim Cholangiocarcinoma has an unimproved prognosis. Interleukin 6 (IL‐6) has an oncogenic potential in some cancer diseases. However, the role of IL‐6 in cholangiocarcinoma carcinogenesis is not well understood. The current study investigated the role of IL‐6 signaling in cholangiocarcinoma carcinogenesis and efficacy of siltuximab treatment on cholangiocarcinoma in vitro and in vivo. Methods The expression of IL‐6 was analyzed on human cholangiocarcinoma cell lines and murine and human cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…IL‐6 is upregulated in cholangiocarcinoma and non‐small cell lung cancer, and treatment with siltuximab alters the IL‐6/STAT3 pathway and suppresses the growth and invasion of tumor. 281 , 282 The results of Phase I/II and II clinical trials conducted by Angevin et al. and Coward et al., respectively, indicated that siltuximab was safe in ovarian and Kirsten rat sarcoma‐2‐mutant cancers treatment.…”
Section: Stat3 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…IL‐6 is upregulated in cholangiocarcinoma and non‐small cell lung cancer, and treatment with siltuximab alters the IL‐6/STAT3 pathway and suppresses the growth and invasion of tumor. 281 , 282 The results of Phase I/II and II clinical trials conducted by Angevin et al. and Coward et al., respectively, indicated that siltuximab was safe in ovarian and Kirsten rat sarcoma‐2‐mutant cancers treatment.…”
Section: Stat3 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…While the antiIL6 antibody siltuximab reduced tumour growth in a xenografted cholangiocarci noma model 153 , it achieved only small effects in multiple myeloma as monotherapy 154 , in combination with the proteasome inhibitor bortezomib 155 and with bortezomib, the cytostatic agent melphalan and the antiinflammatory glucocorticoid prednisone 156 . Siltuximab was also not effective in solid tumours as monotherapy.…”
Section: Interleukin-6mentioning
confidence: 99%
“…Current researches indicate that targeting crosstalk between cells populating local environment and CCA cells is a novel promising approach for the management of CCA. A recent study showed that IL-6 was highly expressed in murine and human CCA tissue, and targeting IL-6 signalling inhibited CCA progression in vitro and in vivo [55]. TGF-beta signaling is also an effective target to suppress CCA cell's proliferation and survival [56].…”
Section: Discussionmentioning
confidence: 99%